El reto de los derechos humanos en la China de los Juegos Olímpicos. El deseo de la universalidad añorada - Berraondo López, Mikel (Huarte de San Juan. Geografía e Historia, 2006)
Being close to the opening ceremony of the next olimpic games in Pekin in 2008, China opened a door to the human rights hope when it assumed a public commitment to improve the situation of those rights before that opening ceremony. So, we are now inmersed in a process that may be crucial for the so declared universality of the human rights, achieving that one of the main reluctant powers to human rights get into the international community of those who protect and guaranteed the ejercise of those rights. Nevertheless the process is complex, taking into account the dramatic situation inside the country, but very interesting, not only because of the changes that will take part in the country, but also thanks to the meaning that this example of China will have for other countries that are far away from the way of protecting human rights.